ANALISIS KELAYAKAN USAHA FOTOCOPY DI SEKITAR LINGKUNGAN KAMPUS UNIVERSITAS RIAU PEKANBARU - Ihsan Bintang MHD; Syapsan Syapsan; Pailis Armas Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Photocopying business is a small business whose implementation does not really require a high level of education, so that it can help open up job opportunities for human resources who have low education and will reduce the unemployment rate. will later encourage people's purchasing power and in time can contribute to the regional economy. Therefore, this study aims to determine the feasibility of a photocopying business around the Riau University, Pekanbaru campus. The population in this study were all photocopying service businesses around the Riau University campus which amounted to 14 photocopying service industries which were also used as research samples. This research uses quantitative descriptive analysis technique or feasibility test. The results of this study indicate that in terms of financial aspects, namely NPV, BC Ratio and IRR for 14 photocopying business actors in the Riau University campus environment, it is feasible to run and from non-financial aspects, namely legal aspects, market aspects, technical and technological aspects and aspects of non-financial aspects. economic and social is also feasible to run.Keywords : Analysis Business Feasibility,, Photocopying Business, UMKM